A conjunctive analysis of false accusations, official misconduct, and race in violent and sexual exonerations cases. (13th June 2022) - Mogavero, Melanie Clark; Hsu, Ko‐Hsin; Bolger, Philip Colin
Abstract: The National Registry of Exonerations tracks cases of individuals who have been convicted and exonerated in the United States since 1989. The objective of the current study was to explore the misconduct patterns in violent and sexual offense cases using a novel method with a focus on cases where suspects were falsely accused, either deliberately or by mistaken witness identification. A conjunctive analysis of case configurations (CACC) was conducted using 1690 males convicted of murder/manslaughter, rape/sexual assault, and child sexual abuse. The results showed that compared to Whites, Blacks had a disproportionate amount of official misconduct in both sexual and non‐sexual homicide cases. Blacks also had a disproportionate amount of misconduct by multiple actors and multiple types. Blacks had more cases of mistaken witness identification and a disproportionate amount of official misconduct in sexual assault cases. Implications and recommendations are discussed.